Household Responses to a Late-Life Job Loss - Bridges, Thomas (Journal of Applied Business and Economics, 2023)
This paper demonstrates that spousal earnings affect an individual’s decision to retire. I find that husbands with higher-earning spouses are more likely to retire following an involuntary job loss. Earlier studies show that job reduces subsequent employment, earnings, and wealth, but they do not explain why some workers return to work and others do not. I add an important dimension to these studies by considering how spousal earnings and household assets affect a worker’s post-displacement labor supply. To explore the household's problem, I develop a stylized two-period model to illustrate how labor supply responds to spousal earnings and household assets in an uncertain environment. Using data from the Health and Retirement Study, I test my theoretical model's predictions using a reduced-form empirical specification. Relative to displaced men with low-earning spouses, husbands with higher-earning wives are more likely to exit the labor force following displacement. The same effect is not detectable in the population of older women. In both populations, a displaced worker with higher household assets is less likely to return to the labor force. At the household level, job loss as a profound impact on retirement well-being. At a broader level, a reduction in the labor supply of older workers has negative fiscal consequences.